Trend analysis of drought indices in the eastern Slovakia. Issue 1 (June 2020) - Nagy, P; Purcz, P; Galas, S; Portela, M M; Hlavatá, Helena; Simonová, Dorota
Abstract: Extreme weather changes have been increasing in the recent times also in the eastern Slovakia. Extremely dry periods alternate with above-average precipitation. In the paper the drought indices were evaluated: Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Index (SPI). Using the non-parametric statistical Mann-Kendall test. The evaluated period was 1960 – 2015 at selected river and climatological stations in the eastern Slovakia. The results showed that no clean significant trends occurred in all evaluated indices and stations.